Cost analysis of leuprorelin acetate in Japanese prostate cancer patients: comparison between 6-month and 3-month depot formulations. (2nd November 2017) - Goto, Rei; Uda, Akihito; Hiroi, Shinzo; Iwasaki, Kosuke; Takashima, Kenta; Oya, Mototsugu
Abstract: Aims: This study aimed to evaluate the economic value for leuprorelin acetate 6-month depot compared with leuprorelin acetate 3-month depot from a societal perspective in Japanese prostate cancer patients. Methods: The cost analysis estimated the reduction in direct and indirect costs as well as intangible costs saved by having one less injection. Claims data were used for the analyses of direct and indirect costs reduction. A discrete choice experiment based on a web-based survey estimated the monetary value of the intangible costs for one injection. Another web-based survey of prostate cancer patients, who had received treatment with leuprorelin acetate injections, was carried out to calibrate the results of the discrete choice experiment. Results: Reductions in medical costs and loss of productivity for having one less injection in prostate cancer patients receiving leuprorelin acetate were JPY 5, 670 and JPY 1, 723, respectively. Intangible costs saved by using a 6-month depot formulation instead of a 3-month depot formulation for the injection of leuprorelin acetate were estimated to be JPY 19, 872, including the values for a reduction in pain (JPY 3, 131), injection site reactions (JPY 11, 545), waiting time (JPY 9, 479), and subtracting the value of medical consultation (JPY 4, 283). The total cost reduction for having one less injection was JPY 27, 265. Limitations: The respondents from the internet panel provided by a survey company are not necessarily a representative population of Japanese society. Conclusions: Leuprorelin acetate 6-month depot has an advantage in monetary value in the reduction in medical costs, loss of productivity, and intangible costs for having one less injection in prostate cancer patients compared with leuprorelin acetate 3-month depot. In the costs for treating with leuprorelin acetate, the percentage of intangible costs might not be negligible. The intangible costs will probably be actively evaluated to proceed to patient-centered healthcare in society.